Translation of patient information leaflets: Trained translators and pharmacists-cum-translators – a comparison - Nisbeth Jensen, Matilde; Korning Zethsen, Karen (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Numerous studies have shown that Patient Information Leaflets (PILs) are generally difficult to understand for ordinary people and that this may be one of the reasons why a high percentage of patients fail to take their medication correctly. A study by Askehave and Zethsen (2002), based on textual analysis and relying on comprehensive extratextual procedural knowledge, has shown that translated Danish PILs were, without exception, more complex than their STs. But why is this so? One possible explanation could be that PILs are very frequently translated by pharmacists, who do not possess the linguistic tools and translational knowledge necessary for expert-to-layman translation or interlingual translation. This article reports on an empirical study that falls into two parts. The first aims to identify possible differences in the translations of these two types of translator in terms of lay-friendliness. The second aims to describe the nature of the differences found between these two types of translator, and discusses whether they could potentially be detrimental to lay-friendliness in PILs.